PENGARUH METODE PENGERINGAN TERHADAP KADAR TOTAL FLAVONOID EKSTRAK ETANOLIK DAUN SINGKIL (Premna corymbosa) - Margareta Retno Priamsari; Odilia Dea Christina; Dwi Setyonugroho (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2022)
The leaves of singkil (Premna corymbosa) empirically contain various secondary metabolite compounds, one of which is flavonoids that can be used as asthma medication, antitumor, worm infection, and reduce bad breath. Drying is one of the stages of making simplicia which is done so that simplicia is not damaged. This study aims to determine the effect of drying method on total flavonoid content in singkil leaf extract. The research method used is experimental. The research phase included sampling, plant determination, drying simplicia with oven temperature of 50oC and drying in an open space protected from indirect sunlight, extraction by maceration, phytochemical screening, determination of total flavonoid content. The assay method used was colorimetric using UV-Vis spectrophotometer with AlCl3 reagent and quercetin standard. The calibration curve was made for 5 concentrations, namely 12.5; 15; 17.5; 20; and 22.5 ppm. The absorbance was calculated at a wavelength of 415 nm and the reading was used as a determinant of the total flavonoid content of the singkil leaf extract. The results showed that the simplicia drying method could significantly affect the total levels of singkil leaf extract, with the total flavonoid content of singkil leaf extract using the drying method of 2.27±0.02% while the total flavonoid content of singkil leaf extract using the 50oC oven method was 1, 50±0.02%.